The effect of the cooperative learning strategy according to the strategy of learning together and the overlapping groups in learning some skills in futsal football (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare educational units according to learning together and overlapping groups in learning some skills in futsal, and knowing the effect of learning together and overlapping groups in learning some skills in futsal, and to identify which of the two styles is best in learning some skills in futsal. The researcher used the appropriate experimental method in solving the research problem and achieving the goals, as the experimental method was chosen by the research community in a deliberate manner, due to the school’s proximity to the researcher’s residence, the presence of a cooperative administration with the researcher, and the presence of a qualified teacher in the school that represents the second-grade students of the intermediate stage from the Al-Fatwa Intermediate School for Boys. The schools of the Baghdad Directorate of Education, Al-Rusafa/3, for the academic year (2021-2022), numbering (105) students. As for the selection of the research sample, it is very important and must be taken care of because the sample must represent the research community in a true and honest way in order to obtain more comprehensive results. Therefore, the sample was chosen randomly, and after the researcher determined the community and their number was (105) students, (24) were excluded. ) of the students who failed and played the game in sports clubs, and students who could not participate because of their poor health and had medical reports to prove that, and (21) students were selected for the exploratory experiment, and the research sample was chosen by lottery and thus the sample consisted of (60) students, (20) students representing class (A) with whom the cooperative learning strategy was used according to learning together, (20) students representing class (B) with whom cooperative learning was used according to overlapping groups, and (20) students representing division (C) who used As a control group, it is practiced according to the strategy followed by the teacher in the school, and the sample percentage of the research community reached (57%). One of the most important conclusions is the improvement in the performance of some basic football skills for the halls of the members of the group that were subjected to the educational curriculum according to learning together. The performance of some basic football skills for halls improved for members of the group that were subjected to the learning curriculum according to the overlapping groups. One of the most important recommendations is the need to use the cooperative learning strategy according to (learning together and overlapping groups) in developing skills in football for halls and the need to confirm the use of these two patterns when learning this age group In particular, it enhances the spirit of enthusiasm and teamwork among the team members